2007
DOI: 10.1007/s10658-007-9134-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of real-time PCR as a method for determining the presence of Verticillium dahliae in different Solanaceae cultivars

Abstract: Real-time PCR was used to detect and quantify Verticillium dahliae and to assess the susceptibility of four Capsicum annuum cultivars (Luesia, Padrón, SCM331 and PI201234) and the Capsicum chinense cv. C118 to this pathogen. The symptoms which developed after infection included stunting and yellowing, and were more acute in the cv. SCM331, which also suffered defoliation in later stages of the disease and in C118, which suffered severe stunting. Quantification of the pathogen DNA in roots 23 and 34 days post-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 29 publications
2
27
0
Order By: Relevance
“…Difference in the degree of aggressiveness among the different isolates suggested high variability among sampling populations independent of their original location. When applied real-time PCR techniques for detecting fungal mycelium in infected pepper, Gayoso et al (2007) found good correlation between the severity of the symptoms displayed by Verticillium-infected plants and the relative amount of fungal DNA measured as fungus/plant DNA ratio.…”
Section: Growth Physiology Metabolism and Fruit Yield Of Pepper Plamentioning
confidence: 99%
“…Difference in the degree of aggressiveness among the different isolates suggested high variability among sampling populations independent of their original location. When applied real-time PCR techniques for detecting fungal mycelium in infected pepper, Gayoso et al (2007) found good correlation between the severity of the symptoms displayed by Verticillium-infected plants and the relative amount of fungal DNA measured as fungus/plant DNA ratio.…”
Section: Growth Physiology Metabolism and Fruit Yield Of Pepper Plamentioning
confidence: 99%
“…It is more accurate and less time consuming than conventional, end-point quantitative PCR because it monitors PCR products before reaction components become limiting. Currently, RT-qPCR technology is commonly used in plant pathology for the precise detection and quantification of pathogens in infected plants and infested soils (reviewed by Schena et al 2004b;Ma and Michailides 2007), and it has been used to quantify V. dahliae DNA as well (Schena et al 2004a;Atallah et al 2007;Gayoso et al 2007). RTqPCR has also been successfully implemented to quantify the biomass of V. dahliae D and ND pathotypes in infected olive plants (Mercado-Blanco et al 2003a;Markakis et al 2009).…”
Section: Pre-planting Measures To Control Vwomentioning
confidence: 99%
“…Pérez-Artés et al 2005;DeBode and Van Poucke 2011;Bilodeau et al 2012) as well as for detection in plant samples (e.g. Schena et al 2004;Karajeh and Masoud 2006;Gayoso et al 2007). So far, however, these protocols have not been developed into procedures for routine screening of planting stock or fields to be planted with crops susceptible to Verticillium wilt.…”
Section: Genetic Diversity and Detection Of V Dahliaementioning
confidence: 99%